Hubungan status gizi berdasarkan lingkar lengan atas (LiLA) dengan tekanan darah pada pasien hipertensi - Amila Amila; Nurul Utami; Agnes Silvina Marbun (Holistik Jurnal Kesehatan, 2020)
Mid‐upper arm circumference (MUAC), nutritional status and blood pressure of patients with hypertensionBackground : Obesity is a factor that affects the increase in blood pressure. Measurement of nutritional status assessment Mid‐upper arm circumference (MUAC), can be used as one of obesity screening. Purpose : To determine the relationship of mid‐upper arm circumference (MUAC), nutritional status and blood pressure of patients with hypertensionMethod: Correlational analytic with cross sectional approach, a sample was recruited with purposive sampling as much as 43 respondents. The data was analyzed by pearson correlation with significance α <0.05.Results : There was a significant correlation mid‐upper arm circumference (MUAC), nutritional status and blood pressure of patients with hypertension with the  systolic blood pressure (p = 0,005, r = 0,420) and diastolic blood pressure (p = 0.025,  r = 0.342).Conclusion: There was a significant correlation mid‐upper arm circumference (MUAC), nutritional status and blood pressure of patients with hypertension and consideration of the research to be implemented as an early detection of obesity to prevent and control excessive weight gain and increase of blood pressureKeywords: Mid‐Upper Arm Circumference (MUAC); Nutritional status; Blood pressure; Patients; HypertensionPendahuluan: Obesitas merupakan faktor yang mempengaruhi peningkatan tekanan darah.Pengukuran status gizi dapat digunakan sebagai salah satu skrining obesitas.Tujuan : Untuk mengetahui hubungan status gizi  (lingkar lengan atas) dengan tekanan darah pada masyarakat Desa Pante Raya Barat Kecamatan Wih Pesam Kabupaten Bener Meriah tahun 2017.Metode : Penelitian analitik korelasi dengan pendekatan cross sectional dan teknik pengambilan sampel purposive sampling sejumlah 43 orang. Data penelitian dianalisis dengan uji korelasi spearman pada α <0.05.Hasil :  Uji statistik menunjukkan ada hubungan yang signifikan antara status gizi berdasarkan lingkar lengan atas dengan tekanan darah sistolik, (p= 0,003 r=-0,437) dan tekanan darah diastolik (p= 0,022 r=0,347). Simpulan : Penelitian ini dapat digunakan sebagai deteksi dini obesitas dalam upaya mencegah dan mengendalikan berat badan yang berlebihan dan peningkatan tekanan darah.